Rancang Bangun Sistem Informasi Penjualan Rumah Nelayan (Simaya) Guna Mendukung Tranformasi Digital Bidang Perikanan - Sabaruddin, Raja; Murni, Sri; Apriyanti, Aan; Ulfa, Maria; Surniya, Surniya (LPPM Universitas Bina Sarana Informatika, 2023)
In the ever-evolving era of digital transformation, this research introduces the concept of the Fisher's Home Information System (SIMAYA) as a solution to support the progress and sustainability of the fisheries sector. SIMAYA is designed to meet the specific needs of fishermen by providing access to relevant information, effective fish stock management, and facilitating online connectivity and marketing. This research is grounded in a profound understanding of the complex challenges faced by fishermen, including the impacts of climate change and market fluctuations. Following the waterfall model approach in software development, SIMAYA is constructed with careful consideration of the stages of analysis, design, implementation, testing, and delivery.Survey methods, interviews, and case studies are employed to identify the needs of fishermen and evaluate the effectiveness of SIMAYA in the field. The results of this research are expected to make a tangible contribution to improving the operational efficiency of fishermen, supporting sustainable fisheries policies, and developing economic ecosystems in coastal communities. This abstract provides a brief overview of the implementation of SIMAYA, aiming to create a positive impact in bringing change to the fisheries sector. With advancing technology, SIMAYA is expected to be an effective tool in advancing the welfare of fishermen and enhancing the sustainability of fisheries resources